Draft Annual Plan 1986-87 Seventh Five Year Plan 1985-90 Centrally Sponsored Schemes Union Territory of Pondicherry - Planning Commission (Planning Commission, 1986)
The main objective of the scheme is to link up the Programme of production and distribution of inputs with that of the technical know-how through well organised institutional field training programmes and formulation of informal voluntary groups to achieve efficient handling of the scarce inputs secured at a considerable cost. The training to acquaint the farmers, farm women and young farmers, with improved facilities to provide adequate knowledge of inputs and enable them to develop skills to handle the inputs most efficiently to maximise the production level.
Government of Pondicherry, Planning and Research Department